Pyramidellid fauna of intertidal zone to shallow depths of Oshoro Bay, Japan sea coast on middle Hokkaido, Japan (Mollusca: Gastropoda: Pyramidellidae - Hori, S.; Iizumi, H. (i>Bulletin of the Hokkaido National Fisheries Research Institute</i, 1997)
In the course of field investigations on benthic organisms at the intertidal zone to 5 m-depth in Oshoro Bay, the Japan Sea coast of middle Hokkaido, the following 13 species belonging to the gastropod family Pyramidellidae were collected: Odostomia desimana Dall and Bartsch, 1906, O. tenera (A. Adams, 1860), O. cf. kizakiensis Yokoyama, 1922, O. cf. toneana Yokoyama, 1922, Chrysallida pseudalveata Nomura, 1936, C. ultralaeta (Nomura, 1936), Miralda scitula (A. Adams, 1860), M. neofelixoides (Nomura, 1936), Phasianema lirata (A. Adams, 1860), Turbonilla yoritomoi Nomura, 1938, Cingulina cingulata (Dunker, 1860), C. terebra (Dunker, 1860), and Syrnola taeniata (A. Adams, 1836). These species except C. cingulata are newly recorded from Hokkaido. Geographical distribution of each species suggests that the pyramidellid fauna around the intertidal zone of Oshoro Bay is mainly composed of warm temperate species, but contains a few boreal and tropical species